IKEA and Wal-Mart: Comparison of Transferable Factory Specific Advantages (FSAs) in Internationalization - Salloum, Hussein (International Journal of Scientific Research and Management (IJSRM), 2021)
This study investigates the cases of two mega size retailers, IKEA and Wal-Mart and their internationalization approaches. Whereas IKEA is a Sweden based company that started in 1934 and expanded to 52 countries by 2021 with 378 stores, Wal-Mart is US based company started in 1962 and expanded throughout 26 countries by 2021 with 11,443 stores.